PENGARUH PENAMBAHAN MOLASES DAN DEDAK SEBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM COKLAT (Pleurotus cystidiosus) - Maesaroh, Deri; Mutakin, Jenal; Tustiyani, Isna (Jurnal Pertanian, 2021)
This study aims was to determine the effect of molasses and rice bran on the planting media to the growth and yield of brown oyster mushrooms (Pleurotus cystidiosus). The study was conducted in Patrol Village, Sirnagalih Village, Cigalontang District, Tasikmalaya Regency, in May until August 2018. The research used Factorial Randomized Block Design (RBD) consisting of two factors and three replications. The first factor is the addition of molasses (M) consisting of four levels, namely m0 = no molasses, m1 = molases 34 cc /ℓ  water, m2 = molases 68 cc /ℓ water, m3 = molases 102 cc /ℓ water. The second factor is giving bran (D) consists of 4 levels, namely d0 = rice pholish 20%, d1 = bran 14% + 6%  rice pholish / kg ingredients, d2 = bran 16% + 4% rice pholish / kg ingredients, d3 = bran 18 % + 2% rice pholish / kg of ingredients. The results showed that there were interactions between doses of molasses and bran on the planting medium on the mycelium growth length of 3, 6, 9, 12, 15 and 18 day after inoculation with the best treatment in bran 20% and no molasses. The addition of bran 18% + 2% rice pholish / kg of material and molases 102 cc/ℓ water significantly affected the number of diameter mushrooms, fungi per baglog in periods I and II, number of fungi per plot I and II, fungal weight per baglog period I and II and mushroom weight per plot in periods I and II.